Profit Maximization of a Crude Distillation Unit - Ali, Syed (2013)
At the scheduling layer, a weekly decision is made to be sent to the optimization layer. Short-term scheduling decisions are implemented on a crude distillation unit to process three blends over a three week period. Operational optimization is carried out to maximize the net profit within the acceptable limits of ASTM D86 temperatures, as the product property, for all products other than the residue. A nonlinear steady state model is used to simulate a crude distillation unit later optimized using sequential quadratic programming (SQP) algorithm. Substantial increase in the profit margin throughout the implementation period was observed.